PENGADAAN KOLEKSI BAHAN PUSTAKA DI PERPUSTAKAAN SEKOLAH TINGGI TEKNOLOGI KEDIRGANTARAAN YOGYAKARTA - Didik Subagia (Jurnal Pustaka Ilmiah, 2017)
This paper discusses the procurement collection in the Library of Yogyakarta Higher Technology College. This paper describes the description of planning activities and the method of procuring a collection of library materials in the Library STTKD Yogyakarta. This research was conducted by Qualitafif method with unstructured interview. Theconclusion of this paper is to try the library materials that have’nt been owned by the library STTKD and add materials that have been owned by the Library STTKD with the number of somewhat small, as for the planning step is the Inventory of library materials, library, setting preference. In addition, several methods of procurement of library materials are done in the following way: buyer, gift, exchange, donations, cooperation, endowments and self-published.